Restoration of Radial Bowing After Elastic Stable Intramedullary Nailing in Pediatric Forearm Fractures: The Importance of Bowing Location in Addition to Magnitude - Osman Görkem Muratoğlu; Hasan Ceylan; Gökhan Güzel; Fatih Günaydın; Fevzi Mehmet Kuyumcu; Mehmet Ali Talmaç; Cem Yıldırım (Journal of Clinical Medicine, 2026)
Background/Objectives: Elastic stable intramedullary nailing (ESIN) is widely used for the treatment of pediatric diaphyseal forearm fractures. Although fracture union is commonly achieved, restoration of physiological radial bowing is essential for optimal forearm biomechanics. Most previous studies have focused on bowing magnitude, whereas the anatomical location of maximal radial bowing has received limited attention. Methods: This retrospective observational study included pediatric patients aged 4–16 years who underwent ESIN for diaphyseal radius and ulna fractures and had a minimum follow-up of 1 year. Postoperative anteroposterior radiographs were analyzed to determine maximal radial bowing (MRB) and the location of maximal radial bowing (LMRB) using standardized radiographic methods. Simultaneous concordance with the literature-derived MRB (6–9%) and LMRB (55–75%) reference ranges was evaluated as an exploratory composite radiographic outcome. Clinical, radiological, and surgical variables were analyzed, and multivariable logistic regression was performed to identify factors associated with the exploratory composite radiographic outcome. Results: A total of 61 patients were included. The mean age was 10.8 ± 2.6 years, and 86.9% were male. Mean MRB was 5.9 ± 0.9%. MRB and LMRB were within the predefined literature-derived reference ranges in 55.7% and 85.2% of patients, respectively, and simultaneous concordance with both ranges was observed in 50.8%. A significant association was identified between MRB and LMRB, indicating that increased bowing magnitude was associated with a more proximally located maximal bow. The injury-to-surgery interval was not independently associated with the exploratory composite radiographic outcome. Despite radiological variability, 95.1% of patients demonstrated excellent or good functional outcomes. Conclusions: In this retrospective cohort, combined evaluation of MRB and LMRB provided a descriptive assessment of postoperative radial alignment. Concordance with both predefined reference ranges was associated with less supination loss; however, no individual radiographic parameter showed a significant correlation with functional outcomes.